Fortaleza, de uma contaminação derivada dos lugares turísticos à transformação dos espaços de moradia em territórios de adoecimento e de morte - Eustogio Wanderley Correia Dantas; Maria Clelia Lustosa Costa; Carlos Lucas Sousa da Silva (Confins)
Covid-19 takes over the world and reaches peripheral metropolises. Following its developments in the central countries of Western Europe and the United States, we analyse what happened in Brazil, with an emphasis on its development in Fortaleza. Based on official data (Plataforma Integra SUS), we built a cartographic base to support our analysis and culminate, consequently, in the understanding of the developments associated with the numbers of confirmed cases and deaths, with repercussions on the age dimension and socioeconomic vulnerability. We glimpse, from them, characterization of a movement representative of the institution of tourist places as territories of dissemination and whose impact on the metropolis transforms living spaces into territories of illness and death. The latter territory stands out, therefore, as representative of the developments of COVID-1 in Brazilian cities, affecting predominantly areas of high socioeconomic vulnerability, located in popular neighbourhoods.